IRRIGATION NETWORK CARDING ISSUES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this article, the irrigation networks were studied and the state of reforms implemented in the sector was analyzed. The issues of mapping irrigation networks were also covered.